Application of dispersion models for evaluating the influence of urban air pollution on human health. (4th August 2014) - Valkonen, E.; Harkonen, J.; Kukkonen, J.; Rantakrans, E.; Jalkanen, L.; Haarala, S.
The main objective of this study is to analyse quantitatively the influence of urban air pollution on the health of children, by (i) analysing the concentrations of pollutants in the atmosphere, (ii) analysing the indoor air concentrations, and (iii) conducting epidemiological surveys. The area considered is Espoo, the neighbouring city of Helsinki. We focus in particular on the influence of urban air pollution on children at some selected day nurseries. This paper addresses the first part of the study, i.e. the application of atmospheric dispersion models for analysing outdoor air quality. Numerical results have been computed with a multiple–source urban area dispersion model, using the meteorological hourly time series for the year 1990. The results show the spatial distribution of the concentrations of carbon monoxide, nitrogen dioxide and sulphur dioxide.